Diagnóstico de Babesiosis en perros (Canis familiaris) en la ciudad de Yantzaza - Aguirre Aguilar, Jamil Alexander (2015)
The purpose of this research was to diagnose babesiosis in dogs from the city of Yantzaza. The canine population of the sector was 1753; the Epi program was used for the calculation of the sample info with the 95% of reliability, obtaining a sample of 83 dogs that came from two veterinary clinics. One of the objectives was to determine the prevalence of Babesia spp with consideration given to the age, gender and race of the dogs. The observation of microscopic babesias using Giemsa staining on peripheral smear; the results obtained are as follows: the total prevalence of canine babesiosis was 76%. With Consideration of age; the highest percentage was obtained in dogs 3 to 4 years old, with 85% dogs, under 1 year and 3 years old with 65% for each. There were found smaller percentages in groups of dogs 5 to 6 years-old and older dogs, 7 years 50% and 60% respectively. Whereas sex; higher prevalence in males was observed with 52% and about a 48% in females. In terms of race; the percentage was higher in the French Poodle, with 83 % and the American Pit Bull Terrier breeds there were 75% and mixed breeds with 63%. The next objective was to relate the clinical symptoms with positive test results to Babesia Giemsa, finding 13% without it, and 87% dogs were positive and symptomatic for asymptomatic. (healthy carriers). Finally a count was made in those symptomatic dogs, noting a 50% of normocytic anemia, followed by a regenerative anemia 38% and 25% respectively hiporregenerative anemia and 38% of them had thrombocytopenia.